2016
DOI: 10.1016/j.jff.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Serviceberry, a berry fruit with growing interest of industry: Physicochemical and quali-quantitative health-related compound characterisation

Abstract: A B S T R A C TAmelanchier canadensis (L.) Medik., commonly called serviceberry, is a potential functional food that is also used for its medicinal purposes. This work evaluated the potential of a cultivated serviceberry species as a functional food by characterising its physicochemical characteristics, antioxidant capacity, vitamin C, phenolics and other phytochemicals selected as health-promoting biomarkers, using high-performance liquid chromatography. The most important compound class identified was polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
4
12
0
2
Order By: Relevance
“…As previously reported by Rogiers and Knowles (), malic acid was also the major organic acid in A. alnifolia fruit and its level was similar to our results. Malic and citric acids have not been identified in the fruits of A. canadensis and the amount of tartaric acid (2.9 g/kg FW) was in the same range as in our samples of juneberry fruits (Donno et al., ). Comparing the content of total sugars with some other berry fruit species, it can be concluded that the total sugars in juneberry (183 g/kg FW) are much higher than in red and black currants (46 to 118 g/kg FW) and gooseberries (78 to 96 g/kg FW) (Mikulic‐Petkovsek et al., ).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As previously reported by Rogiers and Knowles (), malic acid was also the major organic acid in A. alnifolia fruit and its level was similar to our results. Malic and citric acids have not been identified in the fruits of A. canadensis and the amount of tartaric acid (2.9 g/kg FW) was in the same range as in our samples of juneberry fruits (Donno et al., ). Comparing the content of total sugars with some other berry fruit species, it can be concluded that the total sugars in juneberry (183 g/kg FW) are much higher than in red and black currants (46 to 118 g/kg FW) and gooseberries (78 to 96 g/kg FW) (Mikulic‐Petkovsek et al., ).…”
Section: Resultssupporting
confidence: 65%
“…In comparison with blueberries ( Vaccinium corymbosum L.), saskatoon serviceberry ( A. alnifolia ) fruits contain a higher content of calcium, fiber, proteins, magnesium, iron, thiamin, and riboflavin (Mazza, ). In particular, saskatoon berries ( A. alnifolia ) contain a high level of anthocyanins (cyanidin derivatives) (Ozga, Saeed, Wismer, & Reinecke, ), flavonol glycosides (especially different quercetin glycosides) (Jurikova et al., ), hydroxycinnamic acids (caffeic and coumaric acid derivatives) (Lachowicz, Oszmianski, & Pluta, ), and Canadian serviceberry ( A. canadensis ) also tannins (Donno, Cerutti, Mellano, Prgomet, & Beccaro, ). It is known that the composition of various chemical substances in fruits depends on various factors, such as genotype, growth site, climatic conditions, degree of maturity, and so on (Mikulic‐Petkovsek, Schmitzer, Slatnar, Stampar, & Veberic, ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are molecules with demonstrated positive effects against oxidative stress and inhibition of macromolecular oxidation. Moreover, a considerable interest in the potential health-promoting and protective effects of anthocyanin-rich fruits or their derived-products in humans and animals has been recently reported [ 9 ]. These molecules are mainly found in the external layers of the skin while flesh tissue contains little or no anthocyanins [ 10 ] as in Prunus padus fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Bioactive substances were separated on a Kinetex C18 column (4.6 × 150 mm, 5 μm, Phenomenex, Torrance, CA, USA). Five different chromatographic methods were used to analyze the samples, two for polyphenols and one for terpenic compounds, organic acids, and vitamins, respectively [ 9 ]. Several mobile phases were used for compound separation and identification and UV spectra were recorded at different wavelengths, as listed in Table 5 .…”
Section: Methodsmentioning
confidence: 99%
“…It should be due to the presence of high TPC amounts in all the extracts. Several studies reported the relationship between antioxidant activity and phenolic compounds [17][18][19].…”
Section: In Vitro Antioxidant Capacitymentioning
confidence: 99%